Reproductive performance of Angus x Hereford and Brahman x Hereford heifers fed to prebeeding target weights - D.J. Patterson; L.R. Corah; D.D. Simms; J.R. Brethour; W.R. Negus (Kansas Agricultural Experiment Station Research Reports, 1986)
Heifer development as effected by nutrition was evaluated in 148 F Angus x Hereford (A x H) and 148 F Brahman x Hereford (B x H) heifers. Heifers within each breed cross were assigned to one of two energy levels and weight groups. Heifers on the low and high energy-level diets were fed to reach 55 or 65%, respectively, of their projected mature body weights by the start of spring breeding. A higher (P<.05) percentage of A x H heifers had reached puberty by the start of spring breeding; however, their average age at puberty was greater (P<.05) than that of B x H heifers. Weight at puberty, for heifers that cycled prior to the start of spring breeding, did not differ between breed groups. Weight of heifers at puberty was greater with the high-energy than with the low-energy diets. Prebreeding body condition scores of heifers on the two energy levels differed (P<.05) more among the A x H females. The A x H heifers had higher (P<.05) fall pregnancy rates than the B x H heifers (89.2 vs 71.9%). Energy level has no significant effect on fall pregnancy rate of A x H heifers, but B x H heifers on the high-energy level had a higher (P<.05) pregnancy rate than those on the low-energy diet.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Reproductive performance; Target weight; Pregnancy rate